The Religious speech and the Political transformation in Iraq - Jaber Jassim, Falah (International Journal of Psychosocial Rehabilitation, 2020)
Talking about the religious speech and political transformation in Iraqi society leads us to the emergence of the contemporary political state in Iraq in 1921 with the blessing of the United Kingdom of Britain. Since that date, the Iraqi political scene has witnessed a clear impact of religious speech. The political events that the Iraqi scene has witnessed have had a major role in changing their patterns, as it is noticed that the events of the great revolution that happened in Iraq in 1920 as a result of the positions of the religious establishment, whether Shiite or Sunni, that the twentieth revolution had emerged with the “Fatwas” of religious authorities in Karbala and Najaf al-Ashraf, as well as the position of Sunni religious authorities, which supported the position of Shiite authorities toward this revolution. After that, the opinions of religious scientific “Hawzas” with their various sides of life had followed toward political events in Iraq.The political events have continued after that, as the “Ba’ath Party” assumed power in Iraq. In this period, the religious establishment was subjected to some form of persecution and abuse, especially the Shiite religious establishment, through pursuing repressive policies, imprisonment, executions, and displacement of many religious figures in Iraq, including the execution of the martyr Mr. Muhammad Baqir Al-Sadr, as well as the execution of many scientists from the Hawzian scientific houses in Najaf, Karbala, and other governorates of Iraq. As for after the invasion of Kuwait, the religious establishment, especially the religious Hawza in Najaf, insisted on the illegitimacy of the occupation of a brother country that enjoyed independence and sovereignty. Moreover, its opinion on the events of the popular uprising (which is called Sha’aban revelution). After 9/4/2003, the day that witnessed the collapse of the mightiest authority in the Middle East and the occupation forces entering Iraq, the religious establishment had taken a new path that was represented by the leadership of the Iraqi religious legislator in the absence of the authority of the law and took it upon itself the preserving of the territorial integrity of Iraq and the preservation of lives, public and private properties. After the emergence of the signs of power in Iraq after a year of occupation appeared, the speech of the religious establishment was taken in fission. That there was a speech based on the foundations of the spirit of social solidarity, spreading the culture of tolerance and peaceful coexistence between the members of the society with the respecting the other and rejecting the conflict that based on sectarian, religious or nationalistic grounds, while the other direction of religious speech which was built on the basis of sectarian and religious incitement, that is why the Iraqi scene since 2004 to the present day has witnessed an armed conflicts that based on sectarian and religious foundations that left tens of thousands of victims and wasted many natural resources, so we note that the religious speech in Iraq has played a fundamental and active role on the political scene in Iraq, this active role has brought about many changes at the level of the political arena and through the changes that have occurred throughout the contemporary political history in Iraq.This study (the religious speech and political transformation in Iraq) has come on two sides. The first was the theoretical side, which contained three topics. The first topic contained identifying concepts, terms, and basic elements of the research, while the second topic dealt with the religious speech and its implications on the political reality, while the third topic dealt with the religious speech and spreading a culture of tolerance and peaceful coexistence. As for the second side, it contained the fourth topic as it dealt with the research methodology, research tools, research fields, and the research sample. The fifth topic contained the analysis of tables and data, results, suggestions, recommendations, and resources.